Service-learning through a multidisciplinary lens - Billig, Shelley H.; Furco, Andrew (Advances in service-learning research., 2002)
A multidisciplinary investigation of service-learning. The papers are divided into sections on: dimensions of service-learning research; theoretical perspectives on service-learning; service-learning and the disciplines; the impacts on service-learning participants; and future directions.